Development of Technology for Vacuum Surface Conditioning by RF Plasma Discharge Combined With DC Discharge - Kovtun, Yurii; Listopad, Viktor; Baron, Demyan; Kozulia, Mykhailo; Kramsky, Egor; Korovin, Valeriy; Lozin, Oleksiy; Shapoval, Anatoliy; Tarasov, Igor; Siusko, Yevhen; Konotops`kyy, Oleksiy; Bondarenko, Mikhaylo; et al. (Science and Innovation, 2021)
Introduction. It is important to decrease light and heavy impurities influxes towards the plasma volume during the high temperature plasma experiments in fusion devices. This is why the conditioning of the wall inner vacuum surfaces is a basic part of the fusion device operation. Problem Statement. The conventional inner vacuum chamber surface conditioning methods has a significant drawback: sputtering materials in a vacuum chamber. The inner vacuum surfaces can be also conditioned with radio-frequency (RF) discharge plasma, but the conditioning effectiveness is limited by low ion energy. Purpose. The purpose of this research is to develop vacuum surface conditioning technology by the radio frequency plasma combined with DC discharge. Materials and Methods. The noncontact passive method of optical plasma spectroscopy has been used to estimate ion plasma composition. The stainless steel outgassing has been determined in situ with the thermodesorption probe method. The sputtering of the samples has been measured with the weight loss method. Results. The studies of combined discharge have shown that: the anode voltage of combined discharge is lower than in case of the glow discharge; the stainless steel 12Kh18N10T erosion coefficient is about 1.5 times less in the case of combined discharge than in the glow one; the thermal desorption diagnostic of wall conditions in the DSM-1 has shown better efficiency with the combined discharge as compared with the glow discharge. The proposed technology is an original one and has no analogs. Conclusions. The reported research results have shown good prospects for the combined discharge usage for plasma walls conditioning and opportunities for using the combined discharge technology for big fusion machines.